The impact of intraoperative adverse events on orthopaedic surgery residents - Lyons, Madeline M.; Smith, Haley E.; Hamid, Kamran S.; Schiff, Adam P. (International Journal of Research in Orthopaedics, 2022)
Background: The goal of this study was to quantify the impact of intraoperative adverse events on orthopaedics residents to better understand how these occurrences affect resident training. Additionally, the study identified the emotional toll of adverse events on trainees and barriers to reporting. Methods: An anonymous 26 question web-based survey was adapted from the Boston intraoperative adverse events surgeons’ attitude study (BISA) survey to be applicable to orthopaedic residents. The survey was sent to orthopaedic residency program coordinators listed in the Council of Orthopaedic Residency Directors (CORD) database. The coordinators then distributed the survey to each program’s residents and fellows. Results: 77 orthopaedic residents and fellows completed the survey. Almost all (84.4%) reported having been involved in an IAE during their training, and the majority (80.6%) experienced emotional distress as a result. 50.7% of respondents have never been involved in discussions with patients or their family regarding a complication during their training. Conclusions: The majority of residents have experienced emotional distress following an intraoperative adverse event, but residents are not routinely involved in subsequent discussions with patients and families following complications. This represents a significant area for improvement in both supporting and training surgical residents.